2004
DOI: 10.1021/jp0485800
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Absorption Spectra of SSO- Anion in Solid Argon

Abstract: When a high-frequency discharged CS 2 :O 2 :Ar sample was condensed at 4 K, new absorptions at 1003.1 and 567.7 cm -1 were produced. Isotopic substitution ( 13 CS 2 /O 2 , C 34 S 2 /O 2 , CS 2 / 18 O 2 , and mixtures) shows that these new absorptions are due to S-O and S-S stretching vibrations, which involve two inequivalent S atoms and one O atom. The photosensitive behavior and the agreement with frequencies and isotopic frequency ratios from quantum chemical calculations substantiate assignment of these ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…Indeed, most of the standard computational methods and basis sets have been shown to be unable to properly treat this moiety, leading to considerable discrepancies between the experimental and theoretically predicted values for the S@O bond lengths and for the vibrational frequencies associated with this bond [22][23][24][25]. The underestimation of the theoretically predicted frequencies for the S@O stretching vibrations was noticed previously for different types of compounds containing the S@O bond, from simple molecules, as dimethyl sulfate [26], dimethyl sulfite [27] or the SSO À anion [28], to more complex species, like 5-methyl-1H,3H-pyrrolo [1,2c] [1,3]thiazole-6,7-dicarboxylate 2,2-dioxide [29]. Although a good agreement of the experimental and predicted frequencies was achieved for both dimethyl sulfate and sulfite when the B3LYP method was used together with the split valence quadruple-f basis set (aug-cc-pVQZ) [26,27], calculations on pseudosaccharins at this level of theory are currently unpractical due to its excessive computational cost.…”
Section: Introductionmentioning
confidence: 92%
“…Indeed, most of the standard computational methods and basis sets have been shown to be unable to properly treat this moiety, leading to considerable discrepancies between the experimental and theoretically predicted values for the S@O bond lengths and for the vibrational frequencies associated with this bond [22][23][24][25]. The underestimation of the theoretically predicted frequencies for the S@O stretching vibrations was noticed previously for different types of compounds containing the S@O bond, from simple molecules, as dimethyl sulfate [26], dimethyl sulfite [27] or the SSO À anion [28], to more complex species, like 5-methyl-1H,3H-pyrrolo [1,2c] [1,3]thiazole-6,7-dicarboxylate 2,2-dioxide [29]. Although a good agreement of the experimental and predicted frequencies was achieved for both dimethyl sulfate and sulfite when the B3LYP method was used together with the split valence quadruple-f basis set (aug-cc-pVQZ) [26,27], calculations on pseudosaccharins at this level of theory are currently unpractical due to its excessive computational cost.…”
Section: Introductionmentioning
confidence: 92%
“…However, it was found that this is not the case for molecules with SO bonds, where the theory often yields frequencies that underestimate the experimentally observed ones. This behavior has been found even for molecules as simple as SSO [10]. Besides, it is also well known that the accumulated knowledge on the molecular structures, conformational and spectroscopic properties, and chemical reactivity in general, of sulfur compounds is still incipient when compared, for instance, with that of their oxygen analogue compounds.…”
Section: Introductionmentioning
confidence: 94%
“…According to previous analyses, [12][13][14] the vibrational frequencies associated with SdO bond stretches are usually underestimated when calculated both at the DFT (B3LYP) level with the split-valence triple-6-311++G(d,p) basis set and at the MP2 level with the split-valence double-6-31++G(d,p) basis set. This result does not follow the usual trend, which is a general overestimation of vibrational frequencies by this type of calculations.…”
Section: Methodsmentioning
confidence: 96%